Efficacious Factors in Pleural Malignancy Based on Characteristics of Pleural Fluid and Type of Primary Tumor in Shahid Sadouqhi and Shahid Rahmonun Hospitals of Yazd from 2019 to 2021 - Abolhasan Halvani; Sareh Rafatmagham; Dorsa Saeedi (Majallah-i dānishgāh-i ̒ulūm-i pizishkī-i Arāk)
Introduction: In this study, the effective factors in pleural malignancy based on pleural fluid characteristics and the type of primary tumor in Shahid Sadouqhi and Shahid Rahmonun hospitals of Yazd from 2019 to 2021 were evaluated. Methods: In this descriptive study, 98 patients with pleural effusion referred for thoracoscopy to the thoracic surgery department in Shahid Sadouqhi and Shahid Rahmonun hospitals in Yazd were studied from 2019 to 2021. The method of data collection in this research was file reading. Among the patients who underwent thoracoscopy during this period, only patients who had at least one study of pleural fluid thoracentesis and pleural fluid analysis in terms of cytology (White blood cells (WBC) and Red blood cells (RBC)), protein, albumin, Lactate Dehydrogenase (LDH), and pH and after reviewing the biopsy pathology report the pleura of these patients were thoracocentesis. Those who had reported cases of pleural malignancy were included in the study. The database used in this research was a simple questionnaire containing the studied variables. Results: In the examination of the pleural fluid of patients with pleural malignancy, in terms of the WBC level, most of the cases were below 1000 units per cubic milliliter. In terms of the LDH level, most of the cases were more than 1000 units/liter. More than 90% of cases had lymphocytes, and the lowest amount was 62 % of lymphocytes. All cases had exudative pleural fluid, which was exudative mainly due to LDH level and then due to both protein and LDH levels at the same time. Conclusions: According to the findings, in patients with pleural malignancy, pleural effusion is exudative in all cases, mainly due to the effect of LDH in the pleural fluid. On the other hand, the percentage of white blood cells in all Cases of predominant lymphocyte percentage were seen.